Timing and determinants of local residential broadband adoption: Evidence from Ireland - Seán Lyons (The Economic and Social Research Institute (ESRI), 2012)
This article examines the time path of broadband adoption for households in areas that are offered broadband service for the first time and the socioeconomic characteristics of broadband users generally. Using cross-sectional data on broadband take-up and socioeconomic characteristics of small areas in Ireland, linked to GIS data on ADSL availability over time, I find that local penetration growth rates are elevated immediately after service is offered. Local growth rates then decline towards the national average, reaching it after about 3.5 years. The article also includes estimates of the effect of various household characteristics on adoption, finding effects broadly consistent with previous literature. Simultaneity in demand and supply are addressed using 2SLS regression.
Keywords: 330